Sex-dependent differences for larkspur (Delphinium barbeyi) toxicosis in yearling Angus cattle. (17th February 2019) - Green, Benedict T; Keele, John W; Gardner, Dale R; Welch, Kevin D; Bennett, Gary L; Cook, Daniel; Pfister, James A; Davis, T Zane; Stonecipher, Clint A; Lee, Stephen T; Stegelmeier, Bryan L
Abstract: Larkspur ( Delphinium spp.) poisoning is a long-term problem for cattle grazing on rangelands of western North America. Results from preliminary experiments have suggested that differences in larkspur toxicity may exist between heifers and bulls. The objective of this study was to compare the physiological responses of yearling Angus heifers, steers, and bulls with a standardized dose of Delphinium barbeyi and to test the hypothesis that the response is sex dependent. Clinical signs of intoxication, including muscle coordination and function, were measured 24 h after oral dosing with larkspur by walking the cattle at a pace of 5 to 6 km h −1 for up to 40 min on an oval dirt track. Due to the experimental methods used, the variation in susceptibility to larkspur was not quantifiable for walking times of 0 or 40 min or more. Larkspur susceptible animals that were not able to walk (0 min; 36% of the animals) or larkspur resistant animals that walked the entire test period of 40 min (9% of the animals) resulted in censored or truncated data. The statistical methods (censReg and lmec) were used to adjust for data truncation or censoring. The heifers were only able to walk −8.9 ± 3.9 min (65.5% censored on the left) compared with 13.2 ± 3.7 min for bulls and 15.9 ± 2.7 min for steers. When heifers were compared with bulls and steers together, heifers walked 23.4 ± 4.5 min less ( P < 0.0001). Serum alkaloid concentrations were measured immediately before walking, and deltaline concentrations averaged 266 ± 28, 131 ± 20, and 219 ± 28 ng mL −1 for all heifers, steers, and bulls, respectively, and serum methyllycaconitine concentrations averaged 660 ± 46, 397 ± 32, and 612 ± 34 ng mL −1 for all heifers, steers, and bulls, respectively. The relative risk of a zero walk time for yearling heifers is 330% that of yearling bulls ( P = 0.0008). These results suggest that yearling Angus heifers are more susceptible to larkspur intoxication and, when possible, heifers should be kept from grazing larkspur-infested rangelands as a simple management tool to reduce the risk of fatal poisoning.